Problem sekwencyjności we współczesnych stosunkach międzynarodowych wyznaczony przez globalizację - Żukrowska, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The essay deals with sequencing in international relations, a phenomenon noticed by numerous economists and political scientists but not studied in details. Sequencing is considered as a managerial tool helping growing number of countries to join the mainstream of economy what enables them to build their prosperity and form foundations for stabilizing their political systems. Sequencing in the text is tackled from different perspectives starting with definition and scope of the notion, institutional sequencing and sequencing in institutionalization, geographic and developmental approaches, what is followed by sequencing of action and sequencing in liberalization, what further leads to divagation on sequencing in international relations and in transformation of post-communist states. All this leads to the problem of sequencing in the current stage of international relations, characterized by globalization. The findings of the essay are as follows: sequencing in undertaken actions plays an important role in international relations. This is a notion related to numerous spheres of relations, what is mentioned and illustrated by examples of practice. The notion is neither covered in literature, defined. And this essay tries, at least partially, to fill in the gap. The ideas presented here are the first attempt to do it, what can be used in further evolution of the concept as well as polemics with presented standpoint. Both approaches can develop the presented concept. Sequencing concerns past stage of international relations as well as it finds application in the current stage of their development. We can observe it in a process of institutionalization, systemic transformation and inclusion of different groups of countries to the mainstream of world economy. Sequencing refers to development, liberalization of relations of group of countries located in the same region, their integration by widening and deepening, etc... Sequencing supports application of certain solutions, especially when one deals with sequencing of membership in certain international organizations. Sequencing is also a form of supporting political structures that are not able on their own (without support) to conduct changes in their own states. This can be one of the reasons why, until now, this notion was not covered in literature. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 401-416